Amphiphilic core-shell nanoparticles with dimer fatty acid-based aliphatic polyester core and zwitterionic poly(sulfobetaine) shell for controlled delivery of curcumin. Issue 18 (12th December 2017) - Gromadzki, Daniel; Tzankova, Virginia; Kondeva, Magdalena; Gorinova, Cvetelina; Rychter, Piotr; Libera, Marcin; Momekov, Georgi; Marić, Milan; Momekova, Denitsa
ABSTRACT: Multifunctional nanocarriers are gaining increasing research interest as polymeric platforms for targeted drug delivery in cancer therapy and diagnosis. In this work, preparation and characterization of surfactant-free polyester nanoparticles (NPs) from a bio-based poly(butylene sebacate- co -butylene dilinoleate)s, poly(butylene sebacate) (PBSE)/poly(butylene dilinoleate) (PBDL), using nanoprecipitation, is reported. The polymeric nanoparticles (sizes narrowly distributed in a range less than 100 nm) were loaded with curcumin (CURC) with an encapsulation efficiency of 98% and drug loading (DL) content of 5–10% wtdrug /wtpolymer . The CURC-loaded nanoparticles were efficiently coated with a novel poly(sulfobetaine)-type zwitterionic polymer synthesized by nitroxide-mediated polymerization and postpolymerization functionalization step. Free and CURC formulated into noncoated and poly(sulfobetaine)-type zwitterionic polymer-coated nanoparticles were further investigated for cytotoxicity and antioxidant activity in a panel of human cell lines and rat liver microsomes, respectively. Formulated into coated NPs, CURC has superior cytotoxic and antioxidant activity versus the free drug and CURC incorporated in noncoated NPs. In addition, cell viability experiments of nonloaded nanoparticles, both coated and noncoated, demonstrated that developed nanoparticles are nontoxic, making them potentially suitable candidates for systemic passive targeting in cancer therapy, namely for treatment of solid tumors exhibiting high tumor accumulation of NPs due to enhanced permeability and retention effect. Polyzwitterion-coated nanoparticles exhibited slower drug release compared with the noncoated ones (half as much after 24 h) presumably due to the presence of the polymer shell around nanoparticles associated with a wider diffusion layer around the particles. GRAPHICAL ABSTRACT: